Effects of Experiential Learning Program of Community Health Workers on Health Literacy and Preventive Behaviors of Emerging Infectious Diseases and Re-Emerging Infectious Diseases of Respiratory System - Neeranuch Wongcharoen; Thapkwan Srirattayawong; Pitakpong Panta; Kiattisak Ongkulna; Jutapong Teachasub; Tanawat Somboon; Dao Weiangkham (SAGE Publishing, 2024)
Introduction/Objective: Community health workers (CHWs) can be extremely important in many facets of healthcare, especially for marginalized communities. Health Literacy and Preventive Behaviors of Emerging Infectious Diseases and Re-emerging Infectious Diseases of the Respiratory System were important for CHWs in Preventing and Control Diseases. Methods: This quasi-experimental research; a 2 pretest-post group design, aimed to investigate the result of the experiential learning program of the CHWs toward health literacy and preventive behaviors of the infection of emerging and re-emerging diseases of the respiratory system. The samples are 66 CHWs working in Ngao District, Lampang Province which were divided into 2 groups; the experimental and control groups, 33 subjects for each group. The tools used in this research consisted of an experiential learning program for 6 weeks and a questionnaire concerning health literacy and preventive behaviors of emerging and re-emerging diseases in the respiratory system. Results: The experimental group had the mean score of health literacy regarding the prevention of emerging and re-emerging diseases of the respiratory system at the highest level ( X ¯  = 4.52, SD = 0.16) which was higher than before receiving the program which was a high level ( X ¯  = 3.61, SD = 0.32) at the significant level of P  < .001 while the preventive behavior concerning the emerging and re-emerging diseases in the respiratory system was at the highest level ( X ¯  = 4.63, SD = 0.41)and higher than the control group which was at a high level ( X ¯  = 4.36, SD = 0.50) at the significant level of P  < .001. Conclusions: The research results could be a guideline for developing the CHW's potential effectively and proficiently.